Critical Study of DSN-MUI Fatwa No. 86 Concerning Cash Prizes in Fundraising at Sharia Financial Institutions - Aminuddin (International Journal of Economics (IJEC), 2024)
This research is intended to examine the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No. 86 regarding cash prizes in raising funds at sharia financial institutions. This Fatwa requires that gifts given by Islamic financial institutions to customers must be in the form of goods or services, and prohibits gifts in the form of cash. This study aims to examine the effectiveness and implications of the fatwa and explore possible revisions based on input from Islamic banking scholars and practitioners. The research method used is qualitative through a descriptive analytical approach. Primary data includes DSN-MUI fatwa no. 86 of 2012, research results show that the implementation of this fatwa, especially regarding obligations for gifts in the form of goods, brings challenges for Islamic banks, especially in terms of procurement, maintenance and distribution of gifts in the form of goods and so on. Research also finds that prizes in the form of cash are more flexible and attractive to customers, without adding significant cost burdens to Islamic banks. This research suggests a review and possible revision of the DSN-MUI fatwa no. 86, taking into account the mutual benefit of banks and sharia financial customers.